Colonial Switzerland
XI, 334 p.
Keywords: States without former colonies, it has been argued, were intensely involved in colonial practices. This anthology looks at Switzerland, which, by its very strong economic involvements with colonialism, its doctrine of neutrality, and its transnationally entangled scientific community, constitutes a perfect case in point.